Aberrant lipid metabolism as a therapeutic target in liver cancer. (3rd June 2019) - Pope, Evans D.; Kimbrough, Erinmarie O.; Vemireddy, Lalitha Padmanabha; Surapaneni, Phani Keerthi; Copland, John A.; Mody, Kabir
ABSTRACT: Introduction : Hepatocellular carcinoma (HCC) is one of the most common and lethal cancers. Progress has been made in treatment of HCC; however, improved outcomes are much needed. The increased metabolic needs of cancer cells underscore the importance of metabolic pathways in cancer cell survival. Lipid metabolism has a role in HCC development; aberrant overexpression of several key enzymes is seen in many solid human tumors. Areas covered : We discuss aberrant lipid metabolism and the promise of multiple targets, in particular related to HCC treatment. We searched PubMed and clinicaltrials.gov for published and unpublished studies from 2000 to 2019. These terms were used: lipids, fatty acid metabolism, lipid metabolism, liver cancer, HCC, de novo fatty acid synthesis, ATP citrate lyase, stearoyl CoA denaturase, fatty acid synthase, acetyl coenzyme A carboxylase, CD147, KLF4, monoglyceride lipase, AMP activated protein kinase. Expert opinion : The importance of dysregulation of fatty acid synthesis in cancer is a growing area of research. HCC demonstrates significant alteration in lipid metabolism, representing great potential as a target for novel therapeutics. Various agents have demonstrated promising anti-neoplastic activity. This strategy deserves further development for improved outcomes.